The Mediation Role Of Financial Performance On The Relationship Between Good Corporate Governance (GCG) And Corporate Values (Studies On Manufacturing Companies Listed On The IDX In 2019 - 2021) - Sumarto Pongilatan, Aldhi Rio; Handayani, Susi; Mohd Ali, Mazurina (International Environmental Conferrence on Biosustainability Advancement, 2024)
This study aims to determine the mediating role of financial performance in the relationship between good corporate governance and corporate value. The type of data used is quantitative data sourced from secondary data through IDX data. The population in this study were 72 companies. The sampling technique used purposive sampling. Data is analyzed using SEM and processed through WarPLS. The results showed that good corporate governance with proxies of managerial ownership, institutional ownership, and audit committees had no effect on firm value, while an independent board of commissioners had a positive effect on firm value. Financial performance has no effect on firm value, the mediation results show that financial performance has not been able to mediate good corporate governance on firm value, this is because the company has not optimally formed good corporate governance so it is difficult to increase profits and firm value.